National strategies for screening neural tube defects in Saudi Arabia: activating prevention and early intervention - AlEissa, Mariam; Hakami, Wejdan; Dimopoulos, Andreas; Abdul Rab, Saleha; Alsaadoun, Noor; Asim, Zohaib; Jazieh, Cham; Ateq, Khadijah; Alhusseini, Noara (Frontiers in Public Health, 2025)
BackgroundNeural tube defects (NTDs) are serious congenital anomalies affecting the brain and spinal cord. Despite widespread folic acid supplementation and food fortification programs, regions such as Saudi Arabia have not experienced a proportional decline in NTD prevalence. This narrative review evaluates the multifactorial contributors to NTDs, focusing on the effectiveness of current prevention and screening strategies both globally and within Saudi Arabia.Materials and methodsA comparative methodology guided this review, drawing from studies published between 2000 and 2024 sourced from PubMed, Scopus, and the WHO library. Keywords included “neural tube defects,” “folic acid supplementation,” “screening programs,” and “food fortification.” While not a systematic review, PRISMA principles were loosely followed to ensure study relevance and rigor.ResultsGlobally, countries like the United States, Canada, Chile, and Australia have implemented mandatory folic acid fortification and reported NTD reductions ranging from 19 to 78%. South Africa, for example, achieved a 66% decline in NTD-related deaths post-fortification. In Saudi Arabia, similar initiatives have been launched, including folic acid campaigns and food fortification. However, national-level data evaluating their impact remains sparse. Regional disparities in implementation, awareness, and access have limited the success of these measures. Although 80.1% of Saudi women reportedly understand the preventive role of folic acid, uptake and proper timing of supplementation remain inconsistent. Screening services, particularly in rural areas, are not uniformly accessible, reducing early detection rates. Unlike countries such as Australia and Chile, Saudi Arabia lacks a standardized system for tracking and evaluating NTD outcomes.ConclusionThis review concludes that while Saudi Arabia has adopted commendable preventive strategies, the absence of comprehensive data, policy enforcement, and public education limits their effectiveness. Strengthening national monitoring systems, ensuring equitable access to screening, and enforcing mandatory fortification policies modelled on successful international practices are critical. Adopting evidence-based policies supported by robust evaluation frameworks will be essential to reducing the burden of NTDs and improving maternal and child health outcomes in Saudi Arabia.